2011
DOI: 10.1007/s00595-010-4441-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to an early restoration of exercise capacity after major lung resection

Abstract: An early restoration of exercise capacity after lung resection is possible in patients without mediastinal lymph node dissection and in those who have a small thoracotomy wound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Meanwhile, in accordance with previous studies of Bolliger et al (26) and Nezu et al (27), we found that OPEN leaded to a 10% permanent loss in pulmonary function. Several reports suggested that lobectomy patients suffered a significant reduction (15%) of functional reserve at 6 months postoperatively, with almost equal deterioration between lung function and exercise capacity (28,29). Also, for many patients, the risk of impaired quality-of-life after surgery is an important consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in accordance with previous studies of Bolliger et al (26) and Nezu et al (27), we found that OPEN leaded to a 10% permanent loss in pulmonary function. Several reports suggested that lobectomy patients suffered a significant reduction (15%) of functional reserve at 6 months postoperatively, with almost equal deterioration between lung function and exercise capacity (28,29). Also, for many patients, the risk of impaired quality-of-life after surgery is an important consideration.…”
Section: Discussionmentioning
confidence: 99%
“…[1,13] Several reports suggested that lobectomy patients suffered a significant reduction (15%) of functional reserve at 6 months postoperatively, with almost equal deterioration between lung function and exercise capacity. [14,15] Maziak et al reported that, at 6 months after lung transplantation, 6 patients with UDP had an FEV 1 of at least 60% and total lung capacities exceeding 78%. [16] Based on a comparison of our results, we know that in UDP group, all functional variables (FEV 1 , FVC, TLC, and DLCO) decreased significantly from preoperative to 6 months after the operation and significantly more so than in group of control.…”
Section: Discussionmentioning
confidence: 99%
“…A multidimensional therapeutic approach is recommended including pulmonary rehabilitation (6,7) and an adequate level of physical activity (8,9) in order to improve exercise tolerance, health-related QOL as well as surgical candidacy and to decrease surgical morbidity. Recent studies have shown that physical activity may have important benefits on lung cancer patients and survivors (10)(11)(12), regardless of the disease stage (13) or limited physical activity (14,15). Limited physical activity, also known as 'de-conditioning', may cause the heart and muscles to regress and become less efficient.…”
Section: Discussionmentioning
confidence: 99%